THE EFFECT OF CORN SILK EXTRACT (Zea mays) AS BIOLARVICIDES OF Aedes aegypti MOSQUITO LARVAE IN EFFORTS TO CONTROL SPREAD OF DENGUE HEMORRHAGIC FEVER - Rahmad Wahyudi; Harfina Indriani; Yogi Abror (The Indonesian Journal of Public Health, 2021)
Dengue hemorrhagic fever (DHF) is still a serious health problem in the community. DHF is caused by the dengue virus (DENV) and is transmitted by the Aedes aegypti (Ae. aegypti) mosquito, which is the main vector for the virus. In controlling DHF vectors, larvicides are still used. These larvicides contain chemical compounds that have negative side effects affecting      the human body. Therefore, there is a need for natural-based larvacides (biolarvicides). The purpose of this study was to determine the potential of corn silk as a biolarvicide against dengue vector larvae (Aedes aegypti). This study was carried out at the STIKes Ngudia Husada Madura Bangkalan Laboratory and was done by taking corn silk waste samples disposed of as waste from corn farmers and corn traders in Bangkalan Regency. A Thousand samples of Aedes aegypti larvae that had reached instar III were used and divided into five test groups, namely 0 g/L (control), 6.25 g/L, 12.5 g/L, 25 g/L, and 50 g/L . Each group contained 200 larvae. The experiment was repeated 3 times. Data of the number of deaths of Aedes aegypti larvae were collected every 24 hours. The highest dose that could kill Aedes aegypti larvae was at 20 g/L.Keywords     : biolarvicides, corn silk, larvae, Aedes aegypti